Pendampingan Penyusunan Laporan Keuangan dan Digital Marketing untuk Peningkatan Kinerja UMKM Batik Surya Tuban - Hariyanti Hariyanti; Rokhadi Rokhadi; Dede Mariyani (Jurnal Pengabdian Masyarakat Waradin, 2025)
UMKM Batik Surya is one of the UMKM that aims to preserve the traditional batik culture of Tuban Regency, by employing mothers who are in the partner's environment with the aim of helping to improve the standard of living of the surrounding community. On this occasion, Community Service was carried out at UMKM Batik Surya which still uses manual financial records, does not understand how to manage its business finances, how to organize its human resources and has not carried out digital marketing. The purpose of this Community Service is to improve the performance of UMKM Batik Surya through assistance with Financial Reports and Digital Marketing. The methods used are by conducting training, socialization and assistance. After this research, it is hoped that UMKM Batik Surya will experience an increase in sales turnover, be able to calculate its production costs and manage its human resources